The Role of Geographical Area and Entrepreneurs' Personality - Yurrebaso, Amaia; Picado, Eva María; Paiva, Teresa (Frontiers in Psychology, 2021)
This study proposes a line of research on entrepreneurship based on the analysis of personality traits and geographical area. Its objective is to identify whether certain personality traits or sociocultural variables typical of a particular geographical area are what influences those who have already started an entrepreneurial activity to keep it up, in other words, to maintain their entrepreneurial intention. The research results reach a sample of 479 entrepreneurs from two Iberian Peninsula geographical areas. The analyse of the psychometric properties on the Entrepreneurial Orientation Questionnaire (EOQ) identified five dimensions of the enterprising personality. They also evidence that geographical location is a factor that contributes to the development of a determined entrepreneurial profile. The results show that entrepreneurs in the northern area tend to maintain their business than those in the central zone.